2012
DOI: 10.4028/www.scientific.net/amm.212-213.759
|View full text |Cite
|
Sign up to set email alerts
|

Collapse Evolvement Analysis of Upstream Tailings Dam in Flood Situation

Abstract: Very large volume of mined ore materials are processed annually to obtain the various types of minerals that are essential to industrial processes, the upstream tailings dam is usually constructed to store these wastes. But with the increasing of dam quantities, the tailings dam collapsing in flood which are among the most dangerous hazards that affect mountainous and rural areas in a wide range of environments become more and more. Therefore it’s necessary to analyze the collapse mode of upstream tailings dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These standards provide not only a basis for companies to identify and classify hazard sources but also guidance to the government to achieve grading control of hazard sources. Jing et al ( 2012 ) studied the displacement, infiltration line, stress, and damage process using a physical model test and a numerical simulation method. The results showed that physical model trials and numerical simulation analysis are effective means of studying tailings dams.…”
Section: Introductionmentioning
confidence: 99%
“…These standards provide not only a basis for companies to identify and classify hazard sources but also guidance to the government to achieve grading control of hazard sources. Jing et al ( 2012 ) studied the displacement, infiltration line, stress, and damage process using a physical model test and a numerical simulation method. The results showed that physical model trials and numerical simulation analysis are effective means of studying tailings dams.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the principle of similarity, Wu and Qin built a physical model of the Vadogo tailings pond and studied the optimization of the tailings dam maintenance and protection, to reduce the scale of the dam break, the discharged flow rate and flow velocity, and the downstream inundation area, thereby mitigating the destructive impact of dam break events (Wu and Qin, 2018). Jing et al used physical modeling to study the dam displacement, saturation line, stresses, and fracture processes of upstream tailings dams during floods in the past 100 years, thus deepening our understanding of the dam failure regimes (Jing et al, 2012).…”
Section: Introductionmentioning
confidence: 99%